CONSERVATION OF EARTHEN ARCHITECTURE IN THE HUMAHUACA QUEBRADA OF JUJUY, ARGENTINA. - Rotondaro, Rodolfo; José, Néstor; Paterlini, Olga; Ferrari, Mónica (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
This paper presents the results of a project, whose main purpose is to develop a Manual of Architecture and Earthen Construction for the inhabitants of the Humahuaca Quebrada (Ravine), located in the Jujuy Province of Argentina. This manual is intended to be the guidelines for earthen-heritage conservation, and to impart recommendations for new earthen construction. The Quebrada is a territory where earthen architecture is found. This is one of the reasons why it was designated a World Heritage Site by UNESCO in 2003. The project also aims to identify vernacular technologies, in order to properly guide their recovery and insertion into legislation, taking into account that it is a territory affected by earthquakes and geological risks. The methodology considers the collection of bibliographic data, ield surveys, interviews and workshops with local people and organizations, and the design of the manual, including recommendations for recovery and development of earthen architecture in the Quebrada. Places and structures were selected, taking into account popular, state and NGO buildings, to identify the changes in autochthonous patterns and their characteristics. The main features, the architectural and construction facets of some of the studied construction, is described, as well as the features corresponding to their cultural value. Signiicant aspects of the impact of industrial technologies on local traditions are described, and proposals for conservation and development of earthen architectures in the Quebrada are submitted.